Morphogenesis of Cynodon cultivars fertilized with nitrogen (Bioscience Journal, 2020)
To evaluate the biomass flow of two cultivars of Cynodon (Tifton 85 grass and vaquero grass) fertilized with increasing levels of nitrogen (N) (control – without nitrogen; 200; 400 and 600 mg dm-3) under greenhouse conditions, this study was carried out, in a completely randomized design, with factorial arrangement. Forages were examined during three regrowth cycles, with results presented as mean values of the cycles. In the analysis of the effect of nitrogen fertilization, the Tifton 85 grass showed an increasing response to nitrogen levels for the leaf elongation rate (LER). The vaquero grass had a quadractic response for the LER with increasing levels of N. As for the stem elongation rate, there was an increasing linear response in both grasses according to increasing levels of N. The leaf senescence rate (LSR) of the Tifton 85 grass has been enhanced by nitrogen fertilization. The vaquero grass revealed a quadractic response for this variable LSR with nitrogen fertilization, with a minimum value of 0.96 cm tiller-1 day-1 with nitrogen level of 42.5 mg dm-3. The phyllochron and the total number of leaves of both grasses have been influenced by nitrogen fertilization, with downward and upward linear responses, respectively, with increasing levels of nitrogen. For the final mean leaf length (MLL) of both forages, we verified an increasing response with increasing levels of nitrogen. Tifton 85 grass and vaquero grass presented similar LER in the absence of nitrogen, but higher values were observed for the fertilized Tifton 85 grass. The fertilization using nitrogen leads to positive responses of the biomass flow of Tifton 85 grass and vaquero grass under the conditions of the present study.